Effects of non-covalent interactions on the properties of 3D printed flexible piezoresistive strain sensors of conductive polymer composites. Issue 6 (3rd June 2021) - Xiang, Dong; Zhang, Zixi; Han, Zhuohang; Zhang, Xuezhong; Zhou, Zuoxin; Zhang, Jie; Luo, Xia; Wang, Ping; Zhao, Chunxia; Li, Yuntao
ABSTRACT: In this work, flexible piezoresistive strain sensors of carbon nanotubes (CNT)/thermoplastic polyurethane (TPU) conductive polymer composites were prepared using fused filament fabrication (FFF) 3D printing. The constructed porous structure and highly elastic TPU matrix allow the sensors to experience strains up to 30% with great recoverability. The printed sensors exhibited a typical negative piezoresistive effect under compressive strain. The effects of non-covalent modification and loading of CNTs on the mechanical and piezoresistive behavior of sensors were investigated. The introduction of 1-pyrenecarboxylic acid (PCA) increased the dispersibility of CNTs and nanofiller-polymer interfacial interactions, resulting in the excellent sensing performance. A sensor with higher CNT content showed greater sensitivity due to generation of more conductive paths during compression. The gauge factor ( G F ) of the 3 wt% CNT/PCA/TPU sensor increased by 43 and 35 times compared with the 3 wt% CNT/TPU and the 1.5 wt% CNT/PCA/TPU sensors, respectively, when strained at 26% to 30%. In addition, the printed sensor of 3 wt% CNT/PCA/TPU showed great reproducibility over 1500 loading cycles. Some applications in monitoring external loads and motion of the human body were demonstrated. This work provides important information for the property optimization and customizable fabrication of flexible piezoresistive strain sensors. Graphical Abstract: uf0001